2022
DOI: 10.3390/agriculture12111882
|View full text |Cite
|
Sign up to set email alerts
|

Precision Agriculture in Brazil: The Trajectory of 25 Years of Scientific Research

Abstract: Precision agriculture (PA) stands out as an innovative way to manage production resources, increasing the efficiency and the socioeconomic and environmental sustainability of agricultural systems. In Brazil, the principles and tools of PA started to be adopted in the late 1990s. To reveal the scientific trajectory and advances in PA taken over the past 25 years in Brazil, we conducted a comprehensive and systematic literature review. After searching for available peer-reviewed literature, 442 publications were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 126 publications
0
2
0
1
Order By: Relevance
“…El 44 % de los productores agrarios de Churuzapa tiene entre 40 y 49 años de edad; el 31 % tiene entre 33 y 39 años de edad; el 25 % tiene de 50 a más años de edad (figura 1). El 75 % de los productores tiene edad por debajo de 65 años, situación capital en la planificación tecnológica agraria; pues, por ejemplo, la agricultura de precisión (AP) se subraya como una representación creadora de tramitar los recursos productivos, acrecentando la eficiencia y la sostenibilidad socioeconómica y ambiental de los regímenes agrícolas (Cherubin et al, 2022).…”
Section: Resultados Y Discusiónunclassified
“…El 44 % de los productores agrarios de Churuzapa tiene entre 40 y 49 años de edad; el 31 % tiene entre 33 y 39 años de edad; el 25 % tiene de 50 a más años de edad (figura 1). El 75 % de los productores tiene edad por debajo de 65 años, situación capital en la planificación tecnológica agraria; pues, por ejemplo, la agricultura de precisión (AP) se subraya como una representación creadora de tramitar los recursos productivos, acrecentando la eficiencia y la sostenibilidad socioeconómica y ambiental de los regímenes agrícolas (Cherubin et al, 2022).…”
Section: Resultados Y Discusiónunclassified
“…By using GPS-guided machinery and sensors to monitor soil and crop conditions, farmers can apply agrochemicals more efficiently, reducing waste and minimizing runoff into water bodies (Carrer, et. al., 2022, Cherubin, et. al., 2022.…”
Section: Case Studies and Best Practicesmentioning
confidence: 99%
“…Recent data have shown that soybean production reached 388.01 million tons in the 2022/2023 season, representing an increase of approximately 7.7% compared to the previous harvest (Statista 2023). The strong demand from the global market is one of the factors driving large-scale production (CONAB 2022), and farmers meet this need through expanding cultivation areas, increased use of fertilizers, advanced machinery and precision agriculture technologies, as well as an increased application of pesticides for crop disease management (Cherubin et al 2022).…”
Section: Introductionmentioning
confidence: 99%